PROGRAMMING: WHAT SHOULD BE MANDATORY? - Patterson, Sam; Hutchison, Amy (Literacy Today (2411-7862))
The article discusses whether computer programming should be made mandatory in schools. It is said that computer science literacy offers so many benefits to learners that it needs to be mandatory in K-12 schooling. Programming in schools more than solving puzzles and mazes and it is a means of communication and creative expression.